Charred : the complete guide to vegetarian grilling and barbecue - Taylor, Genevieve (Quadrille Publishing, 2019)
The past few years have seen an explosion of interest in cooking over fire, with cooks all over the world seeking to get elemental in their cooking. But fire and smoke doesn't always have to be about hunks of meat. Chargrilling and barbecue are a fantastic way of getting the maximum flavor out of versatile vegetables. If you're bored of beefburgers, or if you're vegetarian and want more than scorched corn and chewy halloumi, then Charred offers up over 70 original, exciting recipes to cater for all your veggie BBQ needs. With sections on Stuffed and wrapped vegetables, Burgers and fritters, Kebabs, Low, slow and smoked, and Sharing Platters, the vegetarian dishes will be the highlight of every meal, with the likes of whole roast cauliflower drenched in spiced garlic butter, griddled radicchio with burrata and figs, or corn on the cob with Cambodian coconut, lime and chilli. Live-fire and BBQ expert Genevieve Taylor has developed these inventive, sensational dishes so that they can just as easily be cooked in a grill pan or conventional oven, year-round. Celebrate the magic that happens when glorious vegetables meet flame!